Hombres receptores de violencia en el noviazgo - Pacheco Maldonado, Karina (2013)
Talking violence is a controversial topic and even more when it talks about gender-based violence. Besides, almost always we refer that this type of violence is only practiced against women, though not, more violence either one genre to another or among the same gender. The present research explored the violence phenomenon in 8 men who have a dating relationship, residing in the Federal District of Mexico or in the Metropolitan Area between 20 and 25 years old. It was applied Rosemberg Self-Esteem Scale and a thematic semi-structured interview. Identifying some violence elements towards men more frequently in dating relationships. It was noted that roles and gender stereotypes in the relationship indicates that man was not allowed to cry and show his feelings; while woman was not associate with being violent, while in fact man passes be receiving and woman generating of violence.